An Iridium Catalytic System Compatible with Inorganic and Organic Nitrogen Sources for Dual Asymmetric Reductive Amination Reactions. (16th November 2021) - Gao, Zhaofeng; Liu, Jingwen; Huang, Haizhou; Geng, Huiling; Chang, Mingxin
Abstract: Asymmetric reductive amination (ARA) is one of the most promising methods for the synthesis of chiral amines. Herein we report our efforts on merging two ARA reactions into a single‐step transformation. Catalyzed by a complex formed from iridium and a steric hindered phosphoramidite, readily available and inexpensive aromatic ketones initially undergo the first ARA with ammonium acetate to afford primary amines, which serve as the amine sources for the second ARA, and finally provide the enantiopure C 2 ‐symmetric secondary amine products. The developed process competently enables the successive coupling of inorganic and organic nitrogen sources with ketones in the same reaction system. The Brønsted acid additive plays multiple roles in this procedure: it accelerates the formation of imine intermediates, minimizes the inhibitory effect of N‐containing species on the iridium catalyst, and reduces the primary amine side products. Abstract : Two successive asymmetric reductive aminations (ARAs) have been merged into one reaction system to generate enantiopure C 2 ‐symmetric secondary amines. The iridium‐phosphoramidite complex successfully manages the dual ARAs by using two distinctly different types of amine sources: an inorganic ammonium salt and an organic primary amine.